The Family Dialogue Culture and Its Obstacles in the Omani Family from the Viewpoint of Teachers in North Eastern Province, Sultanate of Oman - Ali Said Sulayiam AlMatari (Gulf Education and Social Policy Review)
Abstract This quantitative study investigates the level of the culture of dialogue within the Omani family and its hindrances from teachers' perspectives in Ash Sharqiya North Governorate in the Sultanate of Oman. Out of 4516 teachers in the governorate in the academic year 2018-2019, 96 teachers participated in the study. The study used a survey, which included two sections; one assessed the level of the culture of dialogue and the second assessed obstacles of family dialogue. The study revealed that, based on the teachers' perspectives, there was a high level of the culture of dialogue in the Omani family. The level of the obstacles of the family dialogue was low. The major obstacles were family dependency on housemaids, other employees at home, and parents being busy. Further, the study indicated that there were no statistically significant differences at the level of (0.05) in the areas of the culture of dialogue on gender, level of education, social status, and the number of family members. However, a statistically significant difference exists at the level of the culture of dialogue at the gender factor in favor of male teachers. There were no statistically significant differences at the level of (0.05) at the hindrances of the culture of dialogue based on gender, level of education, social status, and the number of family members. The main recommendations were: a) activating the culture of dialogue within educational institutions such as schools, b) the importance of parents' awareness of characteristics of children's development stages c) conducting workshops and seminars for parents and d) enhancing the media role for the importance and advantages of the culture of dialogue.